Thyroglobulin determination on silaneâantibody functionalized interdigitated dielectrode surface to diagnose thyroid tumor - Wang, Y. (Blackwell Publishing Ltd, 2021)
Thyroid cancer appears in endocrine glands and specific to thyroid glands has been reported widely. This work was targeted to identify and quantify thyroglobulin by using antithyroglobulin antibody complexed silane surface on interdigitated electrode (IDE) sensing surface. (3-Aminopropyl)triethoxysilane linker was used to make silane-coupling with antibody and attached on the hydroxylated IDE. This electroanalytical IDE revealed the dose-dependent responses with thyroglobulin concentrations. By getting increments with the thyroglobulin concentrations, the current responses were enhanced concomitantly and the thyroglobulin detection limit was noted as 1Â pM on the linear curve yÂ =Â 0.1311xÂ +Â 0.5386; RÂ²Â =Â 0.9707 with the sensitivity at lower picomolar range. Moreover, the control experiments with thyroid peroxidase and nonimmune antibody cannot yield any response of current, confirming the specific detection of thyroglobulin. This research set-up is useful to determine and quantify the thyroglobulin and diagnose thyroid cancer. Â© 2021 International Union of Biochemistry and Molecular Biology, Inc.